Technology-Based Media Innovation for Students with Special Needs - Maryanti, Rina; Suherman, Yuyus; Juhanaini, J; Meggy, Hendriano; Budiyanto, B; RIZQITA, ALYA JILAN; Bela, Muhammad Rafi Wirdan Assyakir Tandu (Jurnal Asesmen Dan Intervensi Anak Berkebutuhan Khusus, 2024)
The research aims to find out technology-based media innovations for students with special needs. The research method used is a mixed method. The research results show that it is important to create technology-based media innovations for students with special needs. This is because the learning process is easy.